Intention to Purchase Halal Cosmetic Products Using Partial Least Squares - Noor Abd Aziz, Noreen; Wahab, Eta (International Journal of Engineering and Technology, 2018)
Malaysia is a multiracial country with Islam being the largest practiced religion. One of the most important concepts in Islam is the concept of halal. Halal industry plays an important role in the whole world, especially for Muslim society. As the market grows rapidly, cosmetics manufactures have eagerness to dominate the market and come out with a variety of products in order to pursue and satisfy customer simultaneously. Thus, the objective of this paper is to identify the antecedent factors that influence the intention to purchase halal cosmetics products among consumers. In this research, data was analyzed using Partial Least Squares Model Analysis (PLS). Â This finding indicate that intention to purchase halal cosmetic are influenced by attitude, subjective norms, perceived behavioral control and knowledge.Â Â